IMPLEMENTASI ZAKAT DALAM KEHIDUPAN EKONOMI - Sovia Ridha (Alhurriyah, 2010)
The persistence of human life is supported by many factors; one of them is about the existence of income and outcome for somebody to fulfill the need of his necessity and those who are under his responsibility. The incoming source can be obtained either by an effort or giving from another people voluntarily. Zakat is one of the sources that can be obtained from another people then can be used either for consuming for his daily needs or as a financial capital exertion that hopefully it will be spreading out to be bigger someday.